Rise to the Challenge: Examining the Relationship of Swimming & Autism Spectrum Disorders - Kuhfuss, Elizabeth P.; Lucas, Matthew D. (Journal of the American Academy of Special Education Professionals, 2010)
This study examined the personal interactions and experiences of six Virginia-based YMCA Aquatics Directors and Instructors in regards to the instruction of individuals with an Autism Spectrum Disorder (ASD). Overall, the main purpose of this study was to offer more insight into the rising challenges faced within the area of adapted aquatics specifically in relation to persons who are impacted by an ASD. This purpose included a hope that by heightening awareness, more research would be done and individuals would be assisted with greater ease and readiness when it comes to acquiring swim skills with a disability. Findings included a general feeling from instructors that although each had some exposure and experience in regards to the instruction of individuals with an ASD, more support could be beneficial. The manuscript also noted that the area of aquatics is included in the definition of physical education in the special education legislation and thus more importance can be placed on these finding.